Integrasi Pendidikan Islam dan sains Perspektif Ismail Raji Al-Faruqi - Moh Kamilus Zaman; M. Mukhlis Fahruddin (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2023)
The discourse on integration in Indonesia has long been echoed as stated in UUSPN Number 20 of 2003 article 30 which requires the implementation of religious education at all levels of education as a form of shared awareness to achieve a complete quality of life. In the implementation of education, it has two main missions, namely fostering intellectual power and fostering moral power. Synergizing science and Islam (Religion) is something that is very important, even a necessity, because ignoring religious values in the development of science and technology will give birth to tremendous negative impacts. normal. The negative impact of the tendency to ignore values (religious morality) can be seen empirically in corrupt behavior and other things that are done by humans on this earth by using the power of science and technology. This research is a library research (library research) where in this research the researcher uses descriptive analytical method. The descriptive method is used to describe Ismail Al Faruqi's views regarding the concept of Islamization taken from several of his related works. Meanwhile, the analytical method used by researchers is to analyze the extent to which the concept of Islamization is in an effort to integrate science and religion. The results of this discussion indicate that, (First: The Islamization of knowledge initiated by Al-faruqi is to Islamize modern science by means of rehabilitation, revolution, reconstruction (rearranging data) and adjustments to the parts that make it up. To apply the idea of the Islamization of knowledge, Al-Faruqi lays his epistemological foundation on the principle of monotheism which consists of five kinds of units, including: 1). Oneness (unity) of Allah SWT. 2). Unity of creation 3). The unity of truth and knowledge. 4). Unity life. 5). Human unity Second: Educational Integration at UIN Malang Perspective of Al-Faruqi UIN Malang as a pioneer in the establishment of ma'had or student dormitories Developed educational culture adapted to university culture. UIN Malang prefer the Imam Al-Ghazali approach which classifies knowledge into Fardlu 'ain and fardlu Kifayah with the